The capitalist conspiracy an inside view of international banking - Griffin, G. Edward ([S.l.] : American Media, 1971)
Explains his conception of the capitalist conspiracy in which a group of some of the richest people in the world own the money systems of the major non-communist nations. Suggests how Americans should respond in order to dismantle the conspiracy's machine of big government.
Also available in a Malay version titled Konspirasi kapitalis
Bibliographical information is taken from the computer prinout - Bibliofile
Keywords: Capitalists and financiers